Same or different: Narrative retells in bilingual Latino kindergarten children. Issue 2 (3rd April 2018) - Méndez, Lucía I.; Perry, Jamie; Holt, Yolanda; Bian, Hui; Fafulas, Stephen
ABSTRACT: The present study examines the association of micro- and macrostructural components in narrative retells within and across languages in Spanish-English bilingual Latino kindergarten children. Using a within-subject research design, fourteen Spanish-English speaking Latino kindergarten children were individually read a scripted picture book, after which narrative retells were elicited separately in each language using the pictures of the book as an aid. Cross-sectional data of the children's retell transcriptions were coded and analyzed for macrostructure using the narrative scoring scheme and for microstructure by computing the mean length of utterance in words, the number of different words, and the subordination index. Results of the study suggest that elements of macrostructure retells are associated across languages. Microstructure components do not seem to be related across languages but are strongly associated within the same language. Performance in microstructural measures in each language was observed to vary across languages, suggesting that children in the sample acquired the lexical and grammar skills associated with microstructure independently in each of their two languages. Findings from this study have clinical and educational implications for the assessment and instruction of Spanish-English bilingual kindergarten children.